DAMPAK INSENTIF PAJAK FINAL UMKM 1 JULI 2018 TERHADAP PERTUMBUHAN PENERIMAAN PAJAK UMKM DI KPP MALANG SELATAN - Laili Septiani; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2019)
ABTRACTThe purpose of this study is to explain the growth of UMKM tax receipts before and after the stipulation of PP 23 of 2018 at the KPP Pratama Selatan Malang. The method uses the documentation method. published are in UMKM tax receipts and paid Taxpayer organizations 6 months and after the stipulation of PP 23 of 2018 at KPP Pratama Selatan Malang. This study uses normality test data analysis techniques, in this study the data are normally distributed. Data that is normally distributed, then will be analyzed by descriptive statistical test with study show that the growth of UMKM Tax Receipts shows a significance value of 0.065 greater than 0.05 so that it can be concluded according to the growth rate before it is applied and applied to PP 23 of 2018. with a percentage return of 1% to 0.5% this is issued amount of UMKM tax receipts.Keywords: PP 23 of 2018, Tax Revenue Development, UMKM.